Voices of the turtledoves : the sacred world of Ephrata - Bach, Jeff, 1958- (University Park, Pa. : Pennsylvania State University Press ; Göttingen, Germany : Vandenhoeck & Ruprecht, 2003)
"The Ephrata Cloister was a community of radical Pietists founded by Georg Conrad Beissel (1691-1768), a charismatic mystic who had been a journeyman baker in Europe. In 1720 he and a few companions sought a new life in William Penn's land of religious freedom, eventually settling on the banks of the Cocalico Creek in what is now Lancaster County. They called their community "Ephrata," after the Hebrew name for the area around Bethlehem.
Voices of the Turtledoves is a fascinating look at the sacred world that flourished at Ephrata.".
"Today, Ephrata is one of Pennsylvania's premier tourist destinations, located near the heart of Amish country. Visitors are drawn to its magnificent buildings and idyllic setting and imagine a lost oasis of peace and contemplation. Voices of the Turtledoves will appeal to anyone who has visited or is planning a visit to Ephrata, Based on impeccable research, it will also interest students of history, religion, and the communal societies of colonial America."--BOOK JACKET.
1. The Religious Thought of Ephrata / Conrad Beissel -- 2. The Religious Thought of Ephrata / Other Writers -- 3. "Holy Church Practices": Ritual at Ephrata -- 4. Manly Virgins and Virginal Men: Gender at Ephrata -- 5. "God's Holy Point of Rest": Ephrata's Mystical Language in Space and Time -- 6. Roses in the Wilderness: Ephrata's Manuscript Art -- 7. "Heavenly Magic": Hidden Knowledge at Ephrata.
Includes bibliographical references (p. 219-269) and index.
Keywords: Ephrata Cloister; Mysticism -- Pennsylvania -- History